Autoavaliação Institucional Participativa: experiência de um Centro de Educação Infantil (CEI) com os Indicadores de Qualidade da Educação Infantil Paulistana (IQEIP) - Nascimento, Daiane Aparecida Borges do (2020)
The motivation to develop this research arose from the concern on how to identify training demands for the school manager regarding the Quality Indicators of Early Childhood Education in São Paulo (IQEIP). In this context, the IQEIP document proposes the construction of a Participatory Institutional Self-Assessment (AIP) culture aligned with the principle of democratic management. The study investigates the process of implementing AIP through the use of IQEIP in an Early Childhood Education institution in the municipality of São Paulo, understanding the role of managers in this process; and had as specific objectives: understanding how the process of implementing IQEIP occurs according to the perspective of the management team; knowing the influence of the management team for the IQEIP implementation and suggesting training actions for the school manager in order to cooperate with the AIP implementation through the use of the IQEIP. This study considered main regulations of Federal and Municipal Legislation of São Paulo and the literature review was based on the studies of Freire (1967, 1992, 1996, 2000), Zabalza (1998), Campos (1999, 2013) , Dalberg, Moss and Pence (2003), Luck (2009 and 2012), Saul (2010), Placco (2012), Bondioli and Savio (2013), Lima (2013), Paro (2015, 2016 and 2018) to understand the different aspects that involve the establishment of quality in Early Childhood Education. This was a qualitative research in education according to proposed by Lüdke and André (1986) characterized as case study. Bibliographic survey, document analysis and semi-structured interviews with the management team were used as research procedures. Data analysis was based on the Content Analysis proposed by Franco (2012). The research showed that the AIP can be transformative as long as it is a process of reflexive construction with the participation of all parties involved in an act of dialogue, listening and sharing responsibility between all subjects